Peramalan Harga Logam Mulia Antam Satu Gram Menggunakan Metode Arima Kalman Filter - Wulan Milanka Lestari; Teti Sofia Yanti (UNISBA Press, 2023)
Abstract. Forecasting is a process to know a picture in the future based on past data. ARIMA Kalman Filter is a forecasting method that combines analysis using the ARIMA model which is then carried out by applying the Kalman Filter algorithm in optimizing the ARIMA model. Kalman Filter is a set of mathematical equations that offer a computationally recursive and efficient way to estimate the state of a process, in such a way as to minimize the average of the squared errors. The purpose of forecasting is to get a picture of the future value that can be used for decision making, one of which is precious metal investment. In this study, forecasting will be carried out on the price of one gram of Antam's precious metal using the ARIMA Kalman Filter method. Precious metals are referred to as “safe heaven” investment instruments, which means that the value of these investment assets will be maintained. Based on the research results from forecasting data for Antam's Precious Metals price of one gram (before tax) per day at the LM Precious Metals Boutique - Bandung using the ARIMA Kalman Filter method, the best forecasting model is the ARIMA Kalman Filter (1,1,0) model with the equation With the implementation of the Kalman Filter algorithm, the results of forecasting data on the Precious Metals price of one gram (before tax) per day at the LM Precious Metals Boutique – Bandung become more accurate. This is indicated by the decrease in the MAPE value from 45.37% using the ARIMA model (1,1,0) to 38.73% after applying the Kalman Filter algorithm to the ARIMA model (1,1,0). Abstrak. Peramalan adalah suatu proses untuk mengetahui suatu gambaran di masa depan berdasarkan data masa lampau. ARIMA Kalman Filter adalah suatu metode peramalan yang menggabungkan analisis menggunakan model ARIMA yang selanjutnya dilakukan penerapan algoritma Kalman Filter dalam optimalisasi model ARIMA. Kalman Filter merupakan sekumpulan persamaan matematik yang menawarkan cara komputasi rekursif dan efisien untuk mengestimasi state dari sebuah proses, sedemikian rupa sehingga meminimumkan rata-rata dari kuadrat galat. Tujuan dari peramalan adalah mengetahui gambaran nilai masa depan yang dapat dimanfaatkan untuk pengambilan keputusan salah satunya investasi logam mulia. Pada penelitian ini akan dilakukan peramalan terhadap harga satu gram logam mulia Antam menggunakan metode ARIMA Kalman Filter. Logam mulia disebut sebagai instrumen investasi “safe heaven” yang artinya aset investasi tersebut akan tetap terjaga nilainya. Berdasarkan hasil penelitian dari peramalan data harga Logam Mulia antam satu gram (sebelum pajak) per hari di Butik Logam Mulia LM – Bandung menggunakan metode ARIMA Kalman Filter maka didapat model peramalan terbaik adalah model ARIMA Kalman Filter (1,1,0) dengan persamaan . Dengan diterapkannya algoritma Kalman Filter, hasil dari peramalan data harga Logam Mulia antam satu gram (sebelum pajak) per hari di Butik Logam Mulia LM – Bandung menjadi lebih akurat. Hal ini ditunjukan dengan menurunnya nilai MAPE dari 45,37% menggunakan model ARIMA (1,1,0) menjadi 38,73% setelah diterapkan algoritma Kalman Filter pada model ARIMA (1,1,0).